Pelatihan Pembuatan Video Animasi untuk Guru Paud Miftahul Ibad sebagai Media Edukasi Kesehatan Interaktif - Dian Nurjannah; Agustin Wulan Suci Dharmayanti (Fakultas Kedokteran Gigi, Universitas Jember, 2024)
The COVID-19 pandemic, declared to end in 2023 through Presidential Decree Number 17 of 2023, teaches us always to live clean and healthy. The rapid spread of the virus that causes COVID-19 is related to society's inadequacy in practising clean and healthy living. Early childhood children are unique because they prefer interactive learning systems, especially those that involve their audio-visual abilities. Their cognitive development tends to explore and learn through direct experience. Visuals full of images, colours and movement will attract the attention of young children and make it easier for them to describe abstract concepts that are difficult to understand, including how to live a clean and healthy lifestyle. The target audience for this service activity is the Miftahul Ibad Integrated Preschool teacher in Mojoparon Village. This basic cognitive ability is a strong basis for the community service team to teach PAUD teachers how to make animated videos to make it easier to convey material to young children. This service activity was carried out through several methods or stages, namely a) the the preparation and design stage, b) the the implementation stage, and c) the the monitoring and evaluation stage. These three stages were carried out at the Miftahul Ibad Integrated Early Childhood Foundation, Mojoparon Village, Rembang District, Pasuruan Regency, East Java. Community service activities at the Miftahul Ibad Integrated Preschool run smoothly. This activity was carried out in the teacher's room. Community service activities through training in making animated videos about living and healthy behaviour for PAUD teachers via laptop and cellphone devices can be followed well. Hopefully,g will be useful for students in improving clean and healthy behaviour.Keywords: audiovisual; Covid-19; early childhood; video making